Investigation of the oxide phase homogenization in the convective cell while producing vacuum-arc remelting - Bozbiei, Liudmyla; Borts, Boris; Neklyudov, Ivan; Tkachenko, Victor (Eastern-European Journal of Enterprise Technologies, 2016)
Discussion of the requirements for the placement of ZrO2 powder in the cathode, which must be taken into account in the production of ODS steel by vacuum-arc remelting in order to provide the high level of homogenization of the oxide particle is presented. The description of the experimental setup and the cathode structure for vacuum arc remelting of steel, alloyed with oxide nano-powder is given. The role of convective processes in the homogenization of nano-particles in the production of ODS steel is highlighted. The convective flow of liquid metal captures ZrO2 powder particles and carries them throughout its volume. The use of the elementary convective cell with free boundary conditions is proposed for the description of homogenization of the oxide particles. The structure and spatial distribution of the convective mass transfer in the elementary convective cell with the non-planar bottom profile are provided. Spatial distribution of convective flow in the cell is described by the Stokes lines, which are concentrically arranged smooth closed lines, which indicates the formation of convective flow in the form of a single vortex in the cell with free boundary conditions. Near the bottom, the Stokes lines reflect the curved cosine bottom profile. The scenario of vacuum arc melting and convective mixing of ZrO2 nano-particles is formulated. Drops of the material of the cathode with ZrO2 nano-particles fall to the central vertical flow of the ECC. Here, the particles are subjected to the action of the convective flow, which will result in the impact of multidirectional forces: Archimedes force (always directed upwards); gravity force (always directed downwards); friction force (Stokes force) (directed along the liquid velocity vector) on these particles. The Archimedes force depends on the volume, i.e. size, of the particle. Thus, the less the nano–particle size, the lower the buoyancy force. The criterion of overcoming the Archimedes force allows determining the sizes of the particle at which their uniform distribution in the cell volume is possible. It is necessary to provide such conditions: – the deeper the drops get into the cell, the more evenly ZrO2 particles are distributed in the cell volume; – even distribution of ZrO2 particles in the sample volume should be observed for sizes less than 80–100 nm.